2020
DOI: 10.1007/s11739-020-02485-y
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific death in hospitalized individuals infected with SARS-CoV-2: more than just acute respiratory failure or thromboembolic events

Abstract: Infection with SARS-CoV-2 is becoming the leading cause of death in most countries during the 2020 pandemic. The objective of this study is to assess the association between COVID-19 and cause-specific death. The design is retrospective cohort study. We included data from inpatients diagnosed with COVID-19 between March 18 and April 21, 2020, who died during their hospital stay. Demographic, clinical and management data were collected. Causes of death were ascertained by review of medical records. The sample i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
3
26
0
2
Order By: Relevance
“…The study design in seven studies was prospective cohort studies [8,12,[17][18][19][20]22], while the others were all retrospective cohort studies [11,13,15,16,21,[23][24][25]. There were a variety of countries, ranging from the U.S. to European countries, with 2 in the USA [11,24], five in the UK [8,13,15,19,22], 1 in Turkey [18],1 in France [16], 1 in Switzerland [23], 2 in Spain [21,25], 2 in Sweden [12,20], and 1 in the UK and Italy [17]. Of these, 13 study settings were in the hospital [8, 11-13, 15-20, 22, 23, 25] and two were in a nursing home [21,24].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design in seven studies was prospective cohort studies [8,12,[17][18][19][20]22], while the others were all retrospective cohort studies [11,13,15,16,21,[23][24][25]. There were a variety of countries, ranging from the U.S. to European countries, with 2 in the USA [11,24], five in the UK [8,13,15,19,22], 1 in Turkey [18],1 in France [16], 1 in Switzerland [23], 2 in Spain [21,25], 2 in Sweden [12,20], and 1 in the UK and Italy [17]. Of these, 13 study settings were in the hospital [8, 11-13, 15-20, 22, 23, 25] and two were in a nursing home [21,24].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The largest sample size was in Turkey [18], with 18,234 patients, and the smallest was in France [16], with 94 patients. Among all of the included studies, 11 studies used the clinical frailty scale (CFS) as an assessment tool for frailty [8,12,13,15,17,[19][20][21][22][23]25], one used the hospital frailty risk score [18], one used the frailty index [24], one used the palliative performance scale [11] and one used the frail nondisabled questionnaire [16]. Detailed information of adjustment variables for each study was shown in Supplemental Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cohort the effect of RNAemia was not present when adjusting for age, a surrogate for pre COVID-19 risk of death. As the death in COVID-19 is often due to respiratory failure 21 , 25 and the burden of chronic diseases 20 , 26 , viremia mediated extra-pulmonary organ failure may not be the key mechanism of death.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort the effect of RNAemia was not present when adjusting for age, a surrogate for pre COVID-19 risk of death. As the death in COVID-19 is often due to respiratory failure [20,23] and the burden of chronic diseases [19,24], viremia mediated extra-pulmonary organ failure may not be the key mechanism of death.…”
Section: Relation To Other Studiesmentioning
confidence: 99%